SiBakul Jogja Free Shipping: Empowerment to Turn on the Economy of Yogyakarta’s MSMEs in Pandemic Era - Nur Faidati; Muhammad Khozin; Gerry Katon Mahendra (Iapa Proceedings Conference, 2020)
This study focuses on the efforts made by the government to make MSMEs survive and their products accessible to consumers in this pandemic era. The real problem for MSMEs in this pandemic era is rebuilding a sluggish economy due to a number of policies that require people to be at home to reduce the spread of the Covid-19. The research method used in this research is descriptive exploratory qualitative research method. This study uses a desk study and interview technique. Desk studies are carried out through secondary data tracking. Interviews were conducted with regional apparatus organizations (OPD) which handle MSMEs and MSMEs’ actor. From the research conducted, it is known that SiBakul Jogja Free Shipping is enough to be the answer to reviving the economy for MSMEs who are still struggling through the Covid-19 pandemic to get their market back, without visiting consumers or making conventional transactions.